Forest Productivity Research-Case Study of Eastern Part of the Country - Pande, M. C.; Tandon, V. N.; Rawat, H. S. (Indian Forester, 1989)
This paper presents the case study on work done on biomass production of some monocultures raised in eastern part of the country. Comparative total biomass and the timber production of Eucalyptus hybrid, Pinus patula, Pinus kesiya and Cryptomeria japonica have been discussed. Further studies to obtain more reliable and authenticated data on productivity has also been suggested.